(untitled) (PerCursos, 2021)
This article objective is to discuss about affections in contemporary society, especially loneliness, understood as a social symptom. It was developed with critical essay writing methodology, which does not follow the logic way established by a traditional method, but it´s with the search for deep reflections, through the articulation of thoughts of different authors. Discusses affections and loneliness, in the context of their social manifestations, consumerism, individualism, virtual life and positive loneliness. Through this reflection, it is understood that the phenomenon of loneliness is constituted through various social transformations, and that it should not necessarily be synonymous with illness or isolation, but it is present in transformation situations and structuring of human development, helping in socialization process and promoting space for learning.